Aspects of the Safe Use of Antibacterial Drugs in Community-Acquired Pneumonia: the Implications of Drug-Drug Interactions - A. A. Taube; B. K. Romanov; E. V. Shubnikova; R. N. Alyautdin; M. V. Zhuravleva; O. A. Demidova; E. Yu. Demchenkova (Антибиотики и Химиотерапия, 2022)
Background. Drug-drug interactions can seriously affect the safety profile of a drug and are an important problem worldwide. Due to the aging of the population, the increasing frequency of polypharmacy, as well as the spread of self-medication, adverse events that are difficult to identify may occur. It is hard to establish a causal relationship between the administration of a certain drug and the occurrence of an adverse event; it may also lead to the conversion of the adverse event into an adverse drug reaction. The risk of drug-drug interactions increases with combination therapy, as a result of misuse of a drug (off-label use), as well as in the absence of full disclosure from physician and patient about potential drug-drug interactions.One of the ways to detect an adverse reaction to a drug is a method of «spontaneous messages», when notification cards issued according to the regulated form are sent from subjects of drug circulation to the national centers for pharmacovigilance, then to the global database of the World Health Organization VigiBase.The aim of the work was a comprehensive analysis of the content compliance of the information presented in the instructions for the medical use of antibacterial drugs on potential drug-drug interactions with validated signals from the WHO global VigiBase database.Material and Methods. The study used information and analytical comparative non-quantitative, graphical, logical methods of analysis, as well as regression analysis. Objects of the study: instructions for medical use for international generic drugs ampicillin, amoxicillin, azithromycin, clarithromycin.Results. The contents of the instructions for use concerning possible interactions of ampicillin, amoxicillin, azithromycin, clarithromycin upon administration with other drugs were studied. Subsequently, a comparative analysis of the obtained data on drug-drug interactions of antibiotics with other drugs was carried out with signals of drug-drug interactions were validated by VigiBase.Conclusion. The study showed that a detailed description of the risks of potential drug-drug interactions in the instructions for medical use with the aim of informing doctors, patients, and caregivers helps to prevent the use of undesirable combinations, thereby reducing the risk of adverse reactions when drugs are used together. The study found that most of the identified information on the safe use of drugs was missing in the instructions for medical use.